MENYOROTI KOMODIFIKASI AGAMA MELALUI LENSA FENOMENOLOGI EDMUND HUSSERL: MENYOROTI KOMODIFIKASI AGAMA MELALUI LENSA FENOMENOLOGI EDMUND HUSSERL - Ikhwan Galih Ilman; Abd Rahman Hamid; Muhammad Akmansyah; Sudarman (Jurnal Studi Islam, 2025)
Abstract: The phenomenon of religious commodification in contemporary society sparks debate between the reduction of sacred meaning and the emergence of new religious expressions. This article aims to examine this dynamic through the lens of Edmund Husserl's phenomenology, emphasizing the importance of individuals' subjective experiences in understanding religious meaning amidst market forces and digitalization. Using a qualitative-descriptive method, this paper integrates academic literature reviews, empirical studies, and symbolic representations in the public sphere to highlight how religious consciousness remains active and authentic despite appearing in new, commodified forms. Husserlian concepts of epoche (suspension of judgment) and phenomenological reduction are employed to set aside normative evaluations and delve into the essence of spirituality as lived by the subject in their interaction with religious symbols in digital media and popular culture. Findings indicate that digital religious content can enhance the religious understanding of younger generations and serve as a relevant medium for spiritual encounters. Therefore, the study concludes that religious commodification does not always erode spirituality but can instead become a new medium of transcendence, particularly for Muslim youth in Indonesia. This research underscores the necessity of a reflective and empathetic interpretation in understanding digital-era religiosity. Key words: religious commodification, phenomenology, Edmund Husser